2006
DOI: 10.1186/1471-2458-6-234
|View full text |Cite
|
Sign up to set email alerts
|

The impact of workplace risk factors on the occurrence of neck and upper limb pain: a general population study

Abstract: Background: Work-related neck and upper limb pain has mainly been studied in specific occupational groups, and little is known about its impact in the general population. The objectives of this study were to estimate the prevalence and population impact of work-related neck and upper limb pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 28 publications
7
70
0
7
Order By: Relevance
“…This study is in agreement with the results presented since a positive relationship was also found between muscular pain and inadequate postures in the subjects who participated in this study, but in contrast with the results of the authors already mentioned, this study only established this relationship for the dental profession (19). Lindfors et al in 2006 reported that the female group of dentists showed a higher incidence of muscular skeletal disorders; our study showed that the presence of pain was more frequent in females with 83% while in males was only 74%.…”
Section: Discussionsupporting
confidence: 93%
“…This study is in agreement with the results presented since a positive relationship was also found between muscular pain and inadequate postures in the subjects who participated in this study, but in contrast with the results of the authors already mentioned, this study only established this relationship for the dental profession (19). Lindfors et al in 2006 reported that the female group of dentists showed a higher incidence of muscular skeletal disorders; our study showed that the presence of pain was more frequent in females with 83% while in males was only 74%.…”
Section: Discussionsupporting
confidence: 93%
“…Sustained cervical postures at work such as forward head posture [6,15] and sustained neck flexion [2,33,35] have been found in previous research to be associated with neck and shoulder pain. For instance, Cagnie et al [6] reported that office workers who hold their neck in a forward bent posture for a prolonged time have 2.6-fold greater odds of developing neck pain.…”
Section: Discussionmentioning
confidence: 73%
“…Reports of 1-year prevalence vary from 15 to 44% [9,10,33]. Prevalence of neck pain is even higher in office workers than in the general community, reaching levels as high as 50 to 60% [2,6,8,19].…”
Section: Introductionmentioning
confidence: 99%
“…Often holding the neck in a forward bent posture for a prolonged time was positively associated with WMSDs-N. Cagnie et al 29) and Julius Sim et al 30) both reported an odds ratio of 2.0 for the relation between hours of prolonged bending of the neck and neck complaints. An increased risk of WMSDs-N was significantly associated with the increased neck flexion angle.…”
Section: Workplace Factorsmentioning
confidence: 98%